En réponse à Pierre Sauvanet : Le rythme de Bachelard est-il temporel ? - During, Elie (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2024)
Bachelard's main philosophical contribution in Dialectics of Duration is not the anti-Bergsonian claim that time is essentially discontinuous, but rather the rationale behind that claim, namely the idea of a causality of forms and structures operating at a distance, according to a principle of deferred action. The reference to rhythm, particularly in the musical realm, takes on its full meaning from the perspective of this 'formal causality'. But if rhythm is indeed the Bachelardian scheme of duration, a Bergsonian might want to raise a critical question: what is properly temporal about rhythmic schemes? To answer this question, one must return to the central intuition of ‘vertical’ time, the time of simultaneities. Rhythm. Time. Duration. Simultaneity. Formal causality. Music.